Alternatif Metode Wisata Backpacker Pasca Pandemi Di Karimun Jawa - Arnold Yudi Nanlohy; Dimas Pura Dedityatama (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2023)
Tourism is indeed something that many people like, but a limited budget is the main reason for people not to go on a tour. Backpacking is a trip to a place without carrying burdensome items or a suitcase, making it easier to travel from one destination to another. Karimunjawa is one of the tourist destinations favored by the Jepara Regency Government and the Central Java Provincial Government. Still beautiful and preserved nature Karimunjawa is the main attraction. According to Tourist Visit Statistics Data by TIC Jepara (Jepara Tourism Information Center), in 2018 the number of tourists who came to visit Karimunjawa was 137,835 people. With details of 129,679 domestic tourists, and 8,156 foreign tourists. (TIC Jepara, 2018). With this backpacker method, it is hoped that it can become an alternative cheap travel method to increase tourists in Karimun Jawa after the pandemic.